Rosiglitazone Regulates TLR4 and Rescues HO-1 and NRF2 Expression in Myometrial and Decidual Macrophages in Inflammation-Induced Preterm Birth. (December 2017) - Kadam, Leena; Gomez-Lopez, Nardhy; Mial, Tara N.; Kohan-Ghadr, Hamid-Reza; Drewlo, Sascha
Introduction: Elevated inflammation accounts for approximately 30% of preterm birth (PTB) cases. We previously reported that targeting the peroxisome proliferator–activated receptor gamma (PPARγ) pathway reduced the incidence of PTB in the mouse model of endotoxin-induced PTB. The PPARγ has proven anti-inflammatory functions and its activation via rosiglitazone significantly downregulated the systemic inflammatory response and reduced PTB and stillbirth rate by 30% and 41%, respectively, in our model. Oxidative stress is inseparable from inflammation, and rosiglitazone has a reported antioxidative activity. In the current study, we therefore aimed to evaluate whether rosiglitazone treatment had effects outside of inflammatory pathway, specifically on the antioxidation pathway in our model. Methods: Pregnant C57BL/6J mice (E16.5) were treated with phosphate-buffered saline (PBS), rosiglitazone (Rosi), lipopolysaccharide (LPS; 10µg in 200µL 1XPBS), or LPS + Rosi (6 hours after the LPS injection). The myometrial and decidual tissues were collected and processed for macrophage isolation using magnetic cell sorting and F4/80+ antibody. Expression levels of antioxidative factors— Nrf2 and Ho-1 —along with the LPS receptor Tlr4 were quantified by quantitative polymerase chain reaction. The protein levels were assessed by immunofluorescence staining. Results: Both the decidual and myometrial macrophages from the LPS-treated animals showed significantly lowered expression of Ho-1 and Nrf2 and higher expression of Tlr4 when compared to the PBS control group. The macrophages from the animals in the LPS + Rosi group had significantly elevated expression of Ho-1 and Nrf2 and downregulated expression of Tlr4 when compared to the LPS group. Conclusion: Rosiglitazone administration prevents PTB by downregulating inflammation and upregulating antioxidative response.